Tendencies and Prospects of the Ukrainian Nuclear Industrial Complex Development - Liashenko, V.; Shevchenko, V.; Osadcha, N.; Kolomiytsev, O.; Kotko, O. (Економічний вісник Донбасу, 2019)
The article analyzes development trends of the nuclear-industrial complex. Among the main problems of development of nuclear-industrial complex determined inadequate legal framework, lack of investment. the required amount of enriched uranium in nuclear fuel purchased by Ukraine only in the Russian Federation. Russia supplies the stockpile of uranium-235 after enrichment not less than 0.3%.
The necessity of development sequence the stages of the innovation-oriented development of nuclear-industrial complex of Ukraine on the basis of strategic determinants. Directly the nuclear-industrial complex, which is the leading element of the nuclear energy complex of Ukraine can be considered a complex sector of the national economy that includes production of uranium, which forms the basis to meet the needs of nuclear power plants in natural uranium in the medium and long term; Zirconia production, which includes the establishment of the production of zirconium, which is the main structural material for the fabrication of nuclear fuel, given its unique physical properties of the weak interaction with neutron flux in the reactor core; manufacture of ion-exchange materials and to ensure the full production of uranium of Ukraine; production of fuel assemblies and components as a key link in the creation of our own nuclear-fuel cycle; research, design and information support of scientific research. In Ukraine there is no specialized institution that would deal with the coordination of the research questions regarding the development of nuclear-industrial complex.
The contribution of the nuclear-industrial complex of Ukraine in the creation of gross domestic product is not significant, but its role is important in ensuring economic security and achieving energy independence. The basic principles for the development of nuclear-industrial complex should be reflected in the state Program of development of the industry and development strategy of the region. For the development of nuclear-industrial complex, it is advisable to use an innovative approach. This approach is represented as a set of three interconnected units, namely: methodical-information unit; diagnostic-estimated; estimating procedure.
Reasonably necessary to increase the volume of uranium production, increase the level of its enrichment and at the same time to solve environmental issues on waste management . У статті проаналізовано тренди розвитку атомно-промислового комплексу. Серед основних проблем
розвитку атомно-промислового комплексу визначені недосконалість законодавчої бази, відсутність інвестицій. Необхідна кількість, збагаченого урану в ядерному паливі закуповується Україною тільки в РФ. Росія постачає відвал урану-235 після збагачення не менше 0,3%.
Обґрунтовано необхідність розроблення послідовності етапів інноваційно-орієнтованого розвитку атомно-промислового комплексу Україні на основі стратегічних детермінант. Безпосередньо атомно-промисловий комплекс, який є провідною ланкою ядерно-енергетичного комплексу України, можна вважати комплексною галуззю національної економіки, що включає: уранове виробництво, що створює основу для задоволення потреби атомних електростанцій у природному урані на середньо- та довгострокову перспективу; цирконієве виробництво, яке передбачає налагодження випуску цирконію, що є основним конструкційним матеріалом для виготовлення ядерного палива з огляду на його унікальні фізичні властивості слабкої взаємодії з нейтронним потоком в активній зоні реактора; виробництво іонообмінних матеріалів та забезпечення ними в повному обсязі уранове виробництво України; виробництво тепловидільних збірок та комплектувальних виробів як невід’ємної ланки створення власного ядерно-паливного циклу; наукове, проектне та інформаційне супроводження проведення науково-дослідних робіт. В Україні відсутній профільний інститут, який би займався координацією науково-дослідних питань щодо розвитку атомно-промислового комплексу.
Внесок атомно-промислового комплексу України у створення валового внутрішнього продукту не є значним, але його роль важлива щодо забезпечення економічної безпеки та досягнення енергетичної незалежності країни. Основні засади розвитку атомно-промислового комплексу доцільно відобразити у державній Програмі розвитку галузі та в Стратегії розвитку регіону. Для розвитку атомно-промислового комплексу доцільно використовувати інноваційний підхід. Даний підхід представлено як сукупність трьох взаємопов’язаних блоків, а саме: методико-інформаційний; діагностично-орієнтувальний; оціночно-процесуальний.
Обґрунтовано необхідність збільшення обсягу видобутку урану, рівня його збагачення та одночасно рішень екологічних питань щодо утилізації відходів. В статье проанализированы тенденции развития атомно-промышленного комплекса. Основными проб-лемами развития атомно-промышленного комплекса являются несовершенство законодательной базы, отсутствие инвестиций. Необходимое количество обогащенного урана в ядерном топливе закупается Украиной только в РФ. Россия поставляет отвал урана-235 после обогащения до 0,3%. В статье обоснована необходимость разработки последовательности этапов инновационно-ориентированного развития атомно-промышленного комплекса Украины на основе стратегических детерминант.
Непосредственно атомно-промышленный комплекс, который является ведущим звеном ядерно-энергетического комплекса Украины, можно считать комплексной отраслью национальной экономики, которая включает: урановое производство, создающее основу для удовлетворения потребности атомных электростанций в природном уране на средне- и долгосрочную перспективу; циркониевое производство, которое предусматривает налаживание выпуска циркония, что является основным конструкционным материалом для изготовления ядерного топлива, учитывая его уникальные физические свойства слабого взаимодействия с нейтронным потоком в активной зоне реактора; производство ионообменных материалов и обеспечение ими в полном объеме урановое производство Украины; производство тепловыделяющих сборок и комплектующих изделий как неотъемлемого звена создания собственного ядерно-топливного цикла; научное, проектное и информационное сопровождение, проведение научно-исследовательских работ. В Украине отсутствует профильный институт, который бы занимался координацией научно-исследовательских работ по развитию атомно-промышленного комплекса.
Значение и вес атомно-промышленного комплекса Украины в создании валового внутреннего продукта не является значительным, но его роль важна по обеспечению экономической безопасности и достижению энергетической независимости страны. Основные принципы развития атомно-промышленного комплекса целесообразно отразить в государственной Программе развития отрасли и Стратегии развития региона. Для развития атомно-промышленного комплекса целесообразно использовать инновационный подход. Данный подход представлен как совокупность трех взаимосвязанных блоков, а именно: методико-информационный; диагностико-ориентировочный; оценочно-процессуальный.
Обоснована необходимость увеличения объемов добычи урана, уровня его обогащения и одновременно решений экологических вопросов по утилизации отходов.